Perilaku Berwirausaha di Kalangan Mahasiswa Universitas Bina Nusantara (Binus) - Zuraida, Rida; Ayu, K. Gita (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Entrepreneurship developed among BINUS University students is in line with university mission, which is to produce 1 entrepreneur out of 3 graduates. This study aims to find out entrepreneurial behavior among students in BINUS University. The information can be use by University to develop appropriate entrepreneur program based on their behavior. This study takes samples from four departments: Industrial Engineering, Civil Engineering, Architecture, and Mathematics-Statistics. The questionnaire is used as behavioral measurementtools and distributed to active -students in forth department. The result is processed using SPSS software. Based on the results of the questionnaire, there is no significant difference among students of the four departments inacceptance of entrepreneurial activities. Students assume that entrepreneurship is positive things to do which is supported by family, friends, and the University. There is a positive correlation between the desire to start entrepreneurship with the family support (r = .454) and with usage of e-media and e-social networking by students (r = .336). Students also prefer food and beverage, fashion, computer and its accessories, gadgets, education as area of business. The main obstacle in starting entrepreneurial activities is availability of both capital and time. Therefore, the support of BINUS is needed related to capital management, understanding of what it is capital and how to start an entrepreneurship, knowledge concerning the entrepreneurship management. University should help students about how to manage their time between managing the businessand their activities as students.